Fundamentals of applied electromagnetics - Ulaby, Fawwaz T. (Fawwaz Tayssir) 1943-; Ravaioli, Umberto (Always learning., 2015)
Widely acclaimed both in the U.S. and abroad, this authoritative text bridges the gap between circuits and electromagnetics material. Coverage begins with transmission lines, leading students from familiar concepts into more advanced topics and applications. A student-friendly approach, full-color figures and images, and a set of interactive simulations will help students develop a deeper understanding of electromagnetic concepts and applications.